Deep microbial life in high‐quality granitic groundwater from geochemically and geographically distinct underground boreholes. Issue 2 (28th January 2016) - Ino, Kohei; Konno, Uta; Kouduka, Mariko; Hirota, Akinari; Togo, Yoko S.; Fukuda, Akari; Komatsu, Daisuke; Tsunogai, Urumu; Tanabe, Akihumi S.; Yamamoto, Satoshi; Iwatsuki, Teruki; Mizuno, Takashi; et al.
Summary: Deep granitic aquifer is one of the largest, but least understood, microbial habitats. To avoid contamination from the surface biosphere, underground drilling was conducted for 300 m deep granitic rocks at the Mizunami underground research laboratory (URL), Japan. Slightly alkaline groundwater was characterized by low concentrations of dissolved organic matter and sulfate and the presence of > 100 nM H2 . The initial biomass was the highest (∼10 5  cells ml −1 ) with the dominance of Hydrogenophaga spp., whereas the phylum Nitrospirae became predominant after 3 years with decreasing biomass (∼10 4  cells ml −1 ). One week incubation of groundwater microbes after 3 years with 13 C‐labelled bicarbonate and 1% H2 and subsequent single‐cell imaging with nanometer‐scale secondary ion mass spectrometry demonstrated that microbial cells were metabolically active. Pyrosequencing of microbial communities in groundwater retrieved at 3–4 years after drilling at the Mizunami URL and at 14 and 25 years after the drilling at the Grimsel Test Site, Switzerland, revealed the occurrence of common Nitrospirae lineages at the geographically distinct sites. As the close relatives of the Nitrospirae lineages were exclusively detected from deep groundwaters and terrestrial hot springs, it suggests that these bacteria are indigenous and potentially adapted to the deep terrestrial subsurface.